ANALISIS KETERAMPILAN TEKNIK DASAR PERMAINAN BULUTANGKIS PADA SISWA KELAS 5 SDN 173 TANJUNG JABUNG BARAT - Al Madi, Ikhwan; Gani Gelanda; Anggi Ramadani Saputra; Muhammad Darul Ehsan; Ely Yuliawan; Tri Bayu Norito (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by Formal Physical Education (PJOK) learning in schools is constrained by limited time allocation of only 2 lesson hours per week, resulting in significant variation and inconsistency in students' badminton basic technical mastery. Objective: This study aims to determine and analyze the basic technical skills of badminton games in fifth-grade students at SDN 173 Tanjung Jabung Barat. Methodology: This study used a qualitative approach with an interpretive descriptive method. Data were gathered through field observation, interviews, and documentation techniques to understand the phenomenon naturally. Results: The results showed a dualism in the level of movement mastery based on the Three-Stage Model of Motor Learning. In simple basic techniques (racket grip and forehand stroke), the majority of students have mastered them well and approached the autonomous stage. Conversely, in complex techniques (backhand stroke, service, and footwork), students are still in the cognitive stage. Students' main weaknesses were identified in the indicators of accuracy, coordination, and body balance when moving. As a practical implication, badminton extracurricular activities are recommended as the primary intervention medium to provide repetitive training programs to improve these complex techniques.